Pelvic organ prolapse – A hidden disfigurement affecting sexual function - Mundhra, Rajlaxmi; Bahadur, Anupama; Prateek, Shashi; Chawla, Latika; Garg, Deepanshi; Kumari, Purvashi; Jaiswal, Shweta (Asian Journal of Medical Sciences, 2023)
Background: Assessment of sexual function in prolapse cases is important. Studies focusing on relationship between sexual function and pelvic organ prolapse (POP) are sparse. Aims and Objectives: The aim of the study was to evaluate sexual function in women with symptomatic POP. Materials and Methods: Women undergoing surgery for POP were interviewed. Results: Among the 60 cases of POP, 35% of women accepted that they used to find ways to avoid sexual intercourse due to their prolapsed organs. Difficulties faced during intercourse were – pain during intercourse (70%), bleeding/discharge (46.67%), burning sensation (20%), unable to achieve orgasm (30%), and urinary leakage in 10%. Almost 68 % of women felt that sexual frequency was decreased in their husband also. About 27% of women felt that due to their disturbed sexual life, their husband started being irritated and frustrated with some even leaving sex in between (8%). About 30% of cases, women said that their husband was really disturbed with her problems and had started avoiding sexual activities as they feared that this might further aggravate her condition. Conclusion: This study emphasizes need to assess sexual profile in women with POP with a message that there is a definite scope of improvement in this regard.